A duopoly theory of government money production the 1930s and 1940s : a comment - Gochoco, Maria Socorro H.; Williams, Raburn M. (1990)
This study suggests that the bureaucratic perspective provides a framework compared with the public interest perspective from which to interpret the behavior of the FED and the treasury in the 1930s and 1940s. It also applies some basic tenets of monetary theory to refute the assertions of some regarding the conduct of monetary policy in that period.
Includes bibliographical references (page 176).
Keywords: Monetary policy -- United States -- 1930-1940.; Money